Obniżenie wieku rozpoczęcia obowiązku szkolnego – reprezentacje społeczne problemu w debacie publicznej - Zuzanna Zbróg (Problemy Wczesnej Edukacji)
The article shows, on the example of discussion about the lowering of the school age, how it can be analysed by means of communication mechanisms distinctive of the social representation theory (anchoring, objectification) and the procedure of media discourse research in what way the media and citizens create social representations concerning socio-political problems, including educational problems. Social representations as a key tool describing the reality give meanings within the frame of the perceived world and join the private and the public reality. The knowledge encompassed in the representations clarifies the reality. The author’s own analysis included press materials published in the on-line versions of Rzeczpospolita, Gazeta Wyborcza and the web page Interia in years 2013–2014.